The Innervated Gracilis Muscle for Microsurgical Functional Lip Reconstruction Review of the Literature - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Reconstruction of the lower and upper lip should meet both aesthetic and functional requirements, whenever possible. Achievement of these goals presents a major challenge particularly in extensive lip defects requiring microsurgical reconstruction. Successful reconstructive outcomes have been reported using free fasciocutaneous flaps such as composite radial forearm flap or anterolateral thigh flap in conjunction with static tendon slings. In recent years, neurovascular gracilis muscle transfer has been introduced in hopes to overcome noncontractile properties of these flaps and to restore oral competence by muscle contractility. This article reviews the available data on the innervated gracilis muscle transfer for functional lip reconstruction. Tips and techniques gleaned from all of the current literature are discussed.
Keywords: gracilis muscle transfer; lip reconstruction; FOREARM FREE-FLAP; SOFT-TISSUE RECONSTRUCTION; LONGUS FREE-FLAP; ANTEROLATERAL THIGH FLAP; FULL-THICKNESS CHEEK; ADVANCEMENT FLAPS; FACIAL PARALYSIS; NECK DEFECTS; LOWER FACE; TRANSPLANTATION